O erro organizacional: um estudo sobre probabilidades de ocorrências e prevenções nos processos organizacionais - Reyes, Ronie Oliveira (2021)
The critical consequences of internal failures impose a relevant impact on financial sustainability, customer relationships, efficiency of the production process, reputation, safety and competitiveness of organizations. Based on the taxonomy of the Human Factors Classification and Analysis System (HFACS), this study proposed to evaluate types, frequencies and multivariate relationships of failures that affect work processes, producing a statistical scientific diagnosis of the phenomenon of error in organizations. An exploratory quantitative research with 261 questionnaires answered by professionals from different levels and sectors concluded that: 1) most organizational errors occur due to unsafe preconditions of work systems (with emphasis on environmental factors) or aspects related to organizational culture (mainly , absence/adherence to formalized procedures; 2) more than 1/3 of the observed failures are not dealt with by the organizations, and there is a strong association between the omission of a deal and the increasing replication of the same type of error, especially when the deviation is from the organizational culture; 3) errors from unsafe actions, more linked to human failures, are highly sensitive to basic profiles of degree of education, age and time of experience, have low recurrence and are generally treated with reorientation measures